Formation of H3− molecular ions by Three-Body Recombination. Issue 12 (January 2020) - Silva, H da; Dulieu, O; Raoult, M
Synopsis: The simplest triatomic molecular ion H 3 −, is predicted to be stable, but has not yet been directly observed experimentally. He we model its formation via Three-Body Recombination of cold and trapped H − ions colliding with H2 molecules in the presence of a buffer gas of He atoms.